Transformational leadership practices of school principals to improve teacher learning performance: a qualitative case study from an indonesian junior high school - Helita Helita; Sudarwan Danim; Bayu Insanistiyo (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study describes the implementation of a principal’s transformational leadership in improving teacher learning performance at State Junior High School No. 40 Seluma, Indonesia. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observations, and documentation involving the principal, teachers, and school staff. Data were analyzed using Miles and Huberman’s interactive model. The findings show that the principal effectively implemented transformational leadership by translating the school vision into concrete instructional practices, building trust through open communication, providing continuous motivation and support, encouraging teacher innovation, and demonstrating exemplary behavior. These practices contributed to improvements in teacher performance, including lesson planning, instructional implementation, assessment, discipline, and professionalism. The study concludes that transformational leadership plays a significant role in enhancing teacher learning performance and proposes an integrated model linking multiple leadership dimensions to teacher outcomes. Practical Implication,school principals should be trained to apply transformational leadership holistically, focusing on vision alignment, trust-building, teacher motivation, and instructional innovation. Schools should also promote collaborative and supportive environments to sustain teacher performance improvement. Novelty, this study offers an integrated perspective of transformational leadership by examining how its core dimensions operate simultaneously within a real school context, rather than as separate elements. Contribution: The study contributes to educational leadership literature by providing an integrated model that explains how transformational leadership influences teacher learning performance through interconnected dimensions, offering both theoretical insight and practical guidance for improving educational quality.